2021
DOI: 10.1007/s00520-021-06627-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nutritional index and its dynamics after curative treatment are independent prognostic factors on survival in non-metastatic nasopharyngeal carcinoma

Abstract: Purpose: We aimed to identify the prognostic and predictive values of post-treatment prognostic nutritional index (PNI) and PNI dynamics in nasopharyngeal cancer patients (NPC) in this study.Methods: 107 non-metastatic NPC patients were included. PNI was calculated by using the following formula: [10 x serum albumin value (gr/dL)] + [0.005 x total lymphocyte count (per mm3)]. ROC analysis was used for determining prognostic PNI values and univariate and multivariate statistical analyses for prognostic characte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…PNI was developed to assess the preoperative nutritional immune status and postoperative complications in surgical patients and has since been demonstrated to be a reliable prognostic factor for numerous malignancies, such as gastric cancer [ 16 ], intrahepatic cholangiocarcinoma [ 29 ], esophageal cancer [ 30 ], and nasopharyngeal carcinoma [ 31 ]. In the field of sepsis, Wu et al reported that after adjusting for confounding variables, PNI was asserted to be an independent prognostic factor for all-cause mortality at 30 days [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…PNI was developed to assess the preoperative nutritional immune status and postoperative complications in surgical patients and has since been demonstrated to be a reliable prognostic factor for numerous malignancies, such as gastric cancer [ 16 ], intrahepatic cholangiocarcinoma [ 29 ], esophageal cancer [ 30 ], and nasopharyngeal carcinoma [ 31 ]. In the field of sepsis, Wu et al reported that after adjusting for confounding variables, PNI was asserted to be an independent prognostic factor for all-cause mortality at 30 days [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Küçükarda 2022 [55] 143 presenting stage III, IVA, and IVB pharyngeal cancers who were treated with concurrent chemoradiotherapy PNI Patients with ↓ PNI had higher likelihoods of grade 3/4 hematological toxicities, sepsis and toxic death. Patients with ↓ PNI were less probable to tolerate concurrent chemoradiotherapy, even when they treated with a considerably lower dosage of cisplatin, showing a decreased completion rate of planned radiotherapy, or a longer overall radiotherapy treatment time.…”
Section: Pharyngeal Cancermentioning
confidence: 99%
“…The prognostic nutritional index (PNI), which is based on the total lymphocyte count and serum albumin concentration in the patient's peripheral blood, is easy to obtain 9,10 . Published studies have shown PNI to be a prognostic marker for digestive cancers 11,12 . For example, Pinato et al 13 and Wang et al 14 found that a low PNI was an independent predictor of poor overall survival (OS) in patients with HCC.…”
Section: Introductionmentioning
confidence: 99%